Development and Implementation of an End-of-Life Curriculum for Pediatric Residents. (November 2018) - Wilson, Paria M.; Herbst, Lori A.; Gonzalez-del-Rey, Javier
Background: Caring for a child near the end of life (EOL) can be a stressful experience. Resident physicians are often the frontline providers responsible for managing symptoms, communicating difficult information, and pronouncing death, yet they often receive minimal education on EOL care. Objective: To develop and implement an EOL curriculum and to study its impact on resident comfort and attitudes surrounding EOL care. Design: Kern's 6-step approach to curriculum development was used as a framework for curriculum design and implementation. Setting/Participants: Categorical and combined pediatric residents at a large quaternary care children's hospital were exposed to the curriculum. Measurements: A cross-sectional survey was distributed pre- and postimplementation of the curriculum to evaluate its impact on resident comfort and attitudes surrounding EOL care. Results: One-hundred twenty-six (49%) of 258 residents completed the preimplementation survey, and 65 (32%) of 201 residents completed the postimplementation survey. Over 80% of residents reported caring for a dying patient, yet less than half the residents reported receiving prior education on EOL care. Following curriculum implementation, the percentage of residents dissatisfied with their EOL education fell from 36% to 14%, while the percentage of residents satisfied with their education increased from 14% to 29%. The postimplementation survey identified that resident comfort with communication-based topics improved, and they sought additional training in symptom management. Conclusions: The implementation of a longitudinal targeted multimodal EOL curriculum improved resident satisfaction with EOL education and highlighted the need for additional EOL education.